Respon Pertumbuhan Kelapa Sawit Tahap Pre Nursery pada Berbagai Macam Komposisi Media - Siddiq, Amirul (Fakultas Pertanian Universitas Tanjungpura, 2019)
The aim of this research was to determine the best media composition for the growth of palm oil seedlings in the pre nursery stage. This research was conducted at the Tanjungpura University Faculty of Agriculture Research House. This research started on August 18, 2018 until November 13, 2018. The method in this research was a completely randomized design consisting of 4 treatments of organic material : A (Soil + Duck Manure 50%: 50%), B (Soil + Cow Manure 50%: 50%), C (Soil + poultry Manure 50%: 50%), D (Soil + Goat Manure 50%: 50%), for each portion were repeated 6 times and 4 samples of plants. The variables observed in this research was heigh of plant, diameter of hump, volume of root, dry weight of shoot, and dry weight of root. Back on the finding of the experiment it could be deduced that palm oil plants at the pre nursery stage with various types of media composition were effect of variable of height of plant but there is no significant effect to the diameter of hump volume of root, dry weight of canopy, and dry weight of root.